'I GET THIS FEELING LIKE GRAPES BUBBLING THROUGH AND I TRY HARD TO PRESS THEM IN'. A QUALITATIVE STUDY OF PREMONITORY URGES IN CHILDREN WITH TIC DISORDERS. Issue 9 (13th August 2015) - Takon, I; Rickards, H; Chowdhury, U; Sharma, S
Abstract : Objective: To explore whether children affected by tic disorders experience, recognise and are able to describe premonitory urges. Method: Semi-structured interviews were carried out with children to unearth their experiences of living with a tic disorder, alongside exploration of how tics are experienced and whether or not children recognise and are able to describe associated premonitory urges. Participants included 10 children (M= SD=; 4 male and 6 female) referred to the Paediatric Department at the Queen Elizabeth II Hospital, Hertfordshire. All children presented with motor and/or vocal tics that had been present for at least one year at the time of the study. NHS Research Ethics approval was obtained for the study, alongside written consent from the children involved and their parents. Interviews were digitally recorded, transcribed verbatim, and analysed using thematic analysis. Children also completed the Premonitory Urge in Tic Scale (PUTS) to allow further exploration of self-reported urges. Child data was supplemented by parents completing the Yale Global Tic Severity Scale. Results: The mean PUTS score was 24 (SD=9). Parent reports from the YGTSS showed that 50% of the study sample experienced a combination of motor and vocal tics, 30% vocal tics only, and 20% predominantly vocal tics. Parent reports further revealed that 60% of participants had moderate impairment from their tics. Qualitative findings identified two overarching themes relating to (1) awareness of and descriptions of tics and (2) lived experience of premonitory urges. The majority of participants (90%) had an awareness of sensory urges before actual tics and were able to link the sensory urges to the tics. Child age did not influence ability to report the presence of premonitory urges, with all children providing vivid descriptions of feelings of discomfort from the sensory urges. Conclusion: The presence of premonitory urges remains a very important feature in differentiating tic disorders from other movement disorders and there is a need to consider age appropriate methods of obtaining information on premonitory urges in children. Using a qualitative methodology, the current study demonstrates that children younger than 10 years of age have the ability to describe, in detail, the presence of premonitory urges.